Research on distribution characteristics of sedimentary microfacies of a system tract under a high resolution sequence framework: A case study of Qixia Formation in Gaomo block, central Sichuan - Liu, Shimin; Zhou, Lu; Guan, Xu; Chen, Xiao; Wu, Yong; Tan, Lufan; Qiu, Zehua; Qian, Yujie; Zhou, Jianghui (Frontiers in Earth Science, 2023)
In conventional sequence stratigraphy research, owing to the limitation of the resolution of seismic data, strata can only be divided into third order sequences at most on the seismic profile. In this study, the vertical fourth order sequence is divided using the high vertical resolutions of gamma ray (GR), uranium (U), thorium (Th), and potassium (K) curves in the logging curves, and the sequence divided in the depth system is then accurately superimposed on the seismic profile through one dimensional forward modelling. Subsequently, through three dimensional Fourier transform technology, the dip angle and azimuth information of the seismic data in the entire region are scanned to obtain the horizons. Through the progradation and retrogradation characteristics of sediments in the Wheeler system, guided by the sequence framework, the horizontal interpretation of the fourth order sequence system tract is conducted in the entire region. Finally, through attribute optimisation, the root mean square amplitude attribute, with the highest degree of coincidence with well data, is selected to study the evolution characteristics of sedimentary microfacies in different periods in the four system tracts. Notably, the strata of Qixia Formation in the study area can be divided into two fourth order sequences, wherein SQ1 comprised transgressive systems tract 1 (TST1) and high stand systems tract 1 (HST1), and SQ2 comprised TST2 and HST2. With the change in the relative sea level cycle, the strata of Qixia Formation in the study area are developed by overlapping the sedimentary microfacies of the interbank depression, interbank sea, and intraplatform shoal from bottom to top.